Ethno Pedagogy-Based Project Learning Model to Increase Religious Behaviour and Collaboration Skills of Early Childhood - Trimuliana, Ifina; Hapidin, Hapidin; Supena, Asep (Journal of Neonatal Surgery, 2025)
Integrating cultural education into early childhood learning environments has gained significant attention for its potential to enhance holistic development. Ethno-pedagogy, which leverages cultural heritage and practices, is posited to foster young children's religious behavior and collaboration skills. This study aims to develop and implement an ethno-pedagogy-based project learning model to increase early childhood religious behavior and collaboration skills. A mixed-methods approach involving quantitative and qualitative data collection techniques was employed. Participants included early childhood from selected early childhood education institutions. Data were gathered through observations, interviews, and questionnaires. The project-based learning model was designed to incorporate local cultural elements and was evaluated for effectiveness over a specific period. The findings indicated a significant improvement in religious behavior and collaboration skills among the children who participated in the ethno-pedagogy-based project learning activities. Quantitative data analysis showed a notable increase in religious behavior and collaboration skills scores. Qualitative analysis revealed positive feedback from educators and parents, highlighting the children's enhanced understanding and practice of religious values and improved ability to work collaboratively. The ethno-pedagogy-based project learning model effectively enhances early childhood religious behavior and collaboration skills. The study suggests that integrating cultural elements into early childhood education preserves cultural heritage and supports the development of essential behavioral and social skills.